Implementasi Program Sembako pada Masa Pandemi Covid-19 di Tingkat Kelurahan - Sianturi, Rut Royanti; Batubara, Beby Masitho; Angelia, Nina (Universitas Medan Area, 2021)
This study aims to determine the implementation of the basic food program and the obstacles that occur in the basic food program in Sei Sikambing B Village, Medan City. The problem is focused on the lack of equitable distribution and data collection that is not relevant to field data. In order to approach this problem, George Edward III's reference to the theory of implementation is used. The data were collected through observation, interviews, documentation and triangulation and analyzed qualitatively. This study concludes that the implementation of the basic food program during the Covid-19 pandemic in the Sei Sikambing B village, Medan City has not run effectively and optimally. This can be seen from the socialization to the community which is only done once a year, then the use of KPM data that has not been updated because it is still using old data so that KPM who have moved domicile even those who have died still receive the basic food assistance. Obstacles in implementing the basuc food program during inthe sei sikambing b sub-district medan city, namely the inaccuracy of targets such as being economically capable, inconsistency in the distribution schedule, yhe problem of damaged cards, the rejection of data collection/verification from the community.